(untitled) (Journal of Environmental Science and Natural Resources, 2016)
An experiment was conducted at the experimental field of the Bangladesh Agricultural University (BAU) to investigate the effects of dairy farms wastewater irrigation on wheat (Triticum aestivum cv. BARI "Shatabdi") production and soil health during 30 November 2013 through 22 March 2014. Three irrigation and three fertilizer treatments were involved in the experiment. The experiment was laid down in a split-plot design with three replications of the treatments. Various growth and yield data of the crop were recorded. For the effect of irrigation water quality, the highest and the lowest grain yield (2.88 t ha-1 and 2.71 t ha-1) were obtained under I3 and I2, respectively. For the effect of fertilizer, the highest and the lowest grain yield (4.42 t ha-1and 1.59 t ha-1) were obtained under F2 and F0, respectively. The interaction effect between irrigation and fertilizer exerted a significant impact on the grain yield of wheat. Irrigation by wastewater did not significantly alter the quality parameters of the irrigated soils. The raw wastewater supplied more nutrients to the soil of the wheat field. Therefore, it may be used as a source of irrigation and fertilizer for wheat production without any hazard of the soil health. J. Environ. Sci. & Natural Resources, 8(2): 157-162 2015